A qualitative investigation into the results of a discrete choice experiment and the impact of COVID-19 on patient preferences for virtual consultations - Anthony W. Gilbert; Carl R. May; Hazel Brown; Maria Stokes; Jeremy Jones (Archives of Physiotherapy, 2021)
Abstract Objectives To conduct a qualitative investigation on a subset of participants from a previously completed Discrete Choice Experiment (DCE) to understand why factors identified from the DCE are important, how they influenced preference for virtual consultations (VC) and how COVID-19 has influenced preference for VC. Methods A quota sample was recruited from participants who participated in our DCE. We specifically targeted participants who were strongly in favour of face-to-face consultations (F2F - defined as choosing all or mostly F2F in the DCE) or strongly in favour of virtual consultations (VC - defined as choosing all or mostly VC consultations in the DCE) to elicit a range of views. Interviews were conducted via telephone or videoconference, audio recorded, transcribed verbatim and uploaded into NVIVO software. A directed content analysis of transcripts was undertaken in accordance with a coding framework based on the results of the DCE and the impact of COVID-19 on preference. Results Eight F2F and 5 VC participants were included. Shorter appointments were less ‘worth’ travelling in for than a longer appointment and rush hour travel had an effect on whether travelling was acceptable, particularly when patients experienced pain as a result of extended journeys. Socioeconomic factors such as cost of travel, paid time off work, access to equipment and support in its use was important. Physical examinations were preferable in the clinic whereas talking therapies were acceptable over VC. Several participants commented on how VC interferes with the patient-clinician relationship. VC during COVID-19 has provided patients with the opportunity to access their care virtually without the need for travel. For some, this was extremely positive. Conclusions This study investigated the results of a previously completed DCE and the impact of COVID-19 on patient preferences for VC. Theoretically informative insights were gained to explain the results of the DCE. The use of VC during the COVID-19 pandemic provided opportunities to access care without the need for face-to-face social interactions. Many felt that VC would become more commonplace after the pandemic, whereas others were keen to return to F2F consultations as much as possible. This qualitative study provides additional context to the results of a previously completed DCE.